Magnetic circular dichroism of peralkylated tetrasilane conformers - Fogarty, Heather A. (National Academy of Sciences, 2004)
Magnetic circular dichroism (MCD) of five peralkylated tetrasilanes (1–5) conformationally constrained to angles ranging from nearly 0° to 180° and of the open chain tetrasilane Si(4)Me(10) (6) shows a clear conformational dependence and permits the detection of previously hidden transitions. In the tetrasilane CH(2)Si(4)Me(8) (1), with the smallest dihedral angle, comparison of MCD with absorption spectra reveals four low-energy electronic transitions. In the tetrasilanes 2–4, three distinct transitions are apparent. In tetrasilanes 5 and 6, MCD reveals the very weak transition that has been predicted to be buried under the first intense peak and to which the anomalous thermochromism of 6 and other short-chain oligosilanes has been attributed.